On the deflection of a liquid jet by an air-cushioning layer - Moore, M; Whiteley, J; Oliver, J (Cambridge University Press, 2018)
A hierarchy of models is formulated for the deflection of a thin, two-dimensional liquid jet as it passes over a thin air-cushioning layer above a rigid, flat, impermeable substrate. We perform a systematic derivation of the leading-order equations of motion for the jet in the distinguished limit in which the air pressure jump, surface tension and gravity affect the displacement of the centreline of the jet, but not its thickness or velocity. We identify thereby the axial lengthscales for centreline deflection in regimes in which the air layer is dominated by viscous or inertial effects. The derived lengthscales and reduced equations aim to expand the suite of tools available for future analyses of the evolution of lamellae and ejecta in impact problems. Assuming that the jet is sufficiently long that tip and entry effects can be neglected, we demonstrate that the centreline of a constant-thickness jet moving with constant axial speed is destabilised by the air layer for sufficiently small surface tension. Expressions for the fastest growing modes are obtained in both the viscous-dominated air and inertiadominated air regimes. For a finite-length jet emanating from a nozzle, we show that, in one particular asymptotic limit, the evolution of the jet centreline is akin to the flapping of an unfurling flag above a thin air layer. We discuss the distinguished limit in which tip retraction can be neglected and perform numerical investigations into the resulting model. We show that the cushioning layer causes the jet centreline to bend, leading to rupture of the air layer. We discuss how our toolbox of models can be adapted and utilised in the context of recent experimental and numerical studies of splash dynamics.